2014
DOI: 10.1186/1477-5956-12-29
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression and transcription profiles of three strains of Aeromonas salmonicida ssp. salmonicida under normal and iron-limited culture conditions

Abstract: BackgroundAeromonas salmonicida is an important fish pathogen that produces a wide and varied array of virulence factors. Here we used iron deprivation by addition of the chelator 2’2-dipyridyl to induce the expression of several such virulence factors in three isolates of Aeromonas salmonicida (one avirulent and two virulent). By using SDS-PAGE followed by mass spectrometry, we identified proteins that appeared differentially expressed under these conditions. The differential transcription of the identified g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…salmonicida A449 ␤-N-acetylhexosaminidase (ASA_RS14095) gene was designed using the Primer 3 software (http://bioinfo .ut.ee/primer3-0.4.0/primer3/) (forward, TGACCGTACCGACTACACCT; reverse, AAGTGGAAGGTCTTGAGC GG). For the 16S reference gene, we used a previously validated primer pair described previously by Menanteau-Ledouble et al (forward, ATATTGCACAATGGGGGAAA; reverse, GTTAGCCGGTGCTTCTTCTG) (52). The primer pairs were used at a final concentration of 250 nM.…”
mentioning
confidence: 99%
“…salmonicida A449 ␤-N-acetylhexosaminidase (ASA_RS14095) gene was designed using the Primer 3 software (http://bioinfo .ut.ee/primer3-0.4.0/primer3/) (forward, TGACCGTACCGACTACACCT; reverse, AAGTGGAAGGTCTTGAGC GG). For the 16S reference gene, we used a previously validated primer pair described previously by Menanteau-Ledouble et al (forward, ATATTGCACAATGGGGGAAA; reverse, GTTAGCCGGTGCTTCTTCTG) (52). The primer pairs were used at a final concentration of 250 nM.…”
mentioning
confidence: 99%
“…Two inserts were also sequenced that were identical to the ones previously identified (Menanteau-Ledouble et al 2014a;Menanteauledouble et al 2014b). The first was identical to the UDP-3-O-acyl-N-acetylglucosamine and likely originated from the same original insertion event.…”
mentioning
confidence: 71%
“…Two inserts were also sequenced that were identical to the ones previously identified (Menanteau‐Ledouble et al . ; Menanteau‐ledouble et al . ).…”
Section: List Of the Genes Identified In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In A. salmonicida , it has been shown that a number of virulence factors were differentially expressed based on environmental conditions. For example, the Flp/Fap pilin proteins [ 24 ], the enzyme enolase [ 25 ] as well as a number of molecules of the iron acquisition apparatus [ 26 ] have all been shown to be upregulated under iron-deprived culture conditions.…”
Section: Introductionmentioning
confidence: 99%